Using Scrabble to Improve the English Vocabulary Mastery of Non-English Undergraduate Students. - Anthonius, Ferdy; Fransisca Andanti, Maria (Universitas Cokroaminoto Palopo, 2023)
Abstract The problem of mastering English vocabulary is not only a problem for non-English undergraduate students but also non-English undergraduate teachers. There are many ways to improve English vocabulary mastery, including English games. The English game used in this research is scrabble. Scrabble is a medium or tool that is expected to improve students' English vocabulary skills. This study employed the PTK (Classroom Action Research) model which was conducted at STAB Nalanda, Jakarta. The samples used were 27 students of the second semester at STAB Nalanda, and the Classroom Action Research model used followed the Stringer model, namely Look, Think, Act which was carried out in two cycles. The research instruments used in this study were interviews, observations, documentation studies, questionnaires, and test questions. This study shows that the use of scrabble has a positive effect on increasing students' English vocabulary with an initial MEAN of 30 increasing rapidly to a final MEAN of 85.36. In addition, other statistical elements, namely the initial MEDIAN of 35, increased sharply to the final MEDIAN of 87, and the initial MODE of 40, increased sharply to the final MODE of 100. The results of this study show that scrabble can be a superior reference for English teachers as a medium for teaching vocabulary. English in class. Keywords: scrabble, vocabulary mastery, English